Flipped-Differentiated Learning (FDL): Promoting a More Comfortable, Customized, and Meaningful Learning - Kristoforus Gustian (Departement of Mathematics Education, 2025)
The objective of this study is to show the essence, the steps, the opportunities, and the challenges of FDL. The freedom of learning is the core of this new model which promotes more comfortable, customized, and meaningful learning. Meanwhile, the steps are conducted through two big parts of activities which are connected each other shaping one syntax of learning, outside and inside classroom activities. The outside activities started from giving diagnostic assessment, determining group, designing differentiated materials, assigning them to students to have an autonomous learning. It is continued with classroom activities which consisted of building wellbeing, sharing identified needs, presenting students’ work, conclusion, formative/summative assessment, and ended by reflection. The opportunities and challenges discovered include saving time, enhancing teachers’ capability, changing teachers’ mind, and more care of personal needs, meanwhile for the challenges were time consuming, lack of technological competence, and dealing with students behavior when studying independently at home. There are two precious thoughts, namely changing the teachers mind and care of personal needs. This new model emphasizes that student has a right to be treated as they are, not others, they are subject of learning, not the object. Hopefully for the next study will be implemented in some schools to prove the effectiveness of this new model with the complete data and extent context, and also focusing on the challenges faced by the teachers in following the steps.